3(k+4)-6k+4+4=

Simple and best practice solution for 3(k+4)-6k+4+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(k+4)-6k+4+4= equation:


Simplifying
3(k + 4) + -6k + 4 + 4 = 0

Reorder the terms:
3(4 + k) + -6k + 4 + 4 = 0
(4 * 3 + k * 3) + -6k + 4 + 4 = 0
(12 + 3k) + -6k + 4 + 4 = 0

Reorder the terms:
12 + 4 + 4 + 3k + -6k = 0

Combine like terms: 12 + 4 = 16
16 + 4 + 3k + -6k = 0

Combine like terms: 16 + 4 = 20
20 + 3k + -6k = 0

Combine like terms: 3k + -6k = -3k
20 + -3k = 0

Solving
20 + -3k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -3k = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -3k = 0 + -20
-3k = 0 + -20

Combine like terms: 0 + -20 = -20
-3k = -20

Divide each side by '-3'.
k = 6.666666667

Simplifying
k = 6.666666667

See similar equations:

| y=25x^2+20x+4 | | -7v+4(u+3)=21 | | -7y-26=23 | | 8+84p=6+10p | | X^2+4+3y=(x-3)(x+5) | | 130+70+2x+2y=360 | | x^2-15x+13=0 | | -2(1-2y)-y=7 | | 3x+4b=18 | | 0.2x+0.3=0.5 | | 5.8+x+5.8+x/2+3(5.8+x)/2=246.20 | | -17a=-12a-65 | | 84=2x+6+2x | | 3-v=12 | | 5(4x+3)=30 | | 0=-x^2+6x-5 | | 20w+2w+w+3w-24w=16 | | 65+.06c=48+.10c | | 17q-14q=9 | | 12-.5h=18-.2h | | 4x^2+60=11 | | -2(-9+2x)=-2 | | 5y+6x=90 | | -3+8-21=7+7 | | 8(4.00+x)=72 | | 24=3[n-5] | | y=-6(0)-9 | | 6m^2-2m-5= | | X^4-6x^3+21x^2-14x-40=0 | | -14y-20y= | | 9u-8u=11 | | 30=5[x+1] |

Equations solver categories